2018
DOI: 10.1097/ncc.0000000000000480
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Health Education Intervention on Jordanian Participants’ Colorectal Cancer Knowledge, Health Perceptions, and Screening Practices

Abstract: This study may provide Jordanian and other nurses with a theory-based educational intervention to improve the quality of nursing care and reduce costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 23 publications
1
18
0
1
Order By: Relevance
“…However, interventions that utilised colonoscopy as the primary screening test [18] or followed-up a positive HRFQ with a colonoscopy [32] had the lowest response rates (16.5 and 14%, respectively). Individual or group education was part of the screening intervention in six studies [21,31,[33][34][35][36] though 2/ 6 studies focused only on education and did not offer screening -participants had to take a stool test independently [31,35]. Visual information about stool collection (e.g.…”
Section: Intervention (Education/screening)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, interventions that utilised colonoscopy as the primary screening test [18] or followed-up a positive HRFQ with a colonoscopy [32] had the lowest response rates (16.5 and 14%, respectively). Individual or group education was part of the screening intervention in six studies [21,31,[33][34][35][36] though 2/ 6 studies focused only on education and did not offer screening -participants had to take a stool test independently [31,35]. Visual information about stool collection (e.g.…”
Section: Intervention (Education/screening)mentioning
confidence: 99%
“…Findings from studies providing education/ educational materials were mixed. Interventions that provided an educational component only and suggested that participants should complete an FOBT but did not offer a stool test as part of the intervention reported much lower FIT/FOBT completion rates (35.7 and 26.0%) [31,35] compared to interventions that offered an educational component and a stool test (in 3/4 interventions) (i.e. 80-100% [34], 74% [21] and 96% [36]).…”
Section: Intervention (Education/screening)mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the effectiveness of CRC screening and the availability of CRC screening tests, overall screening rates are low, and the pace of screening progression is slow (Bidouei et al, 2014;Ferlay et al, 2014;Reyes and Miranda, 2015;Bray et al, 2018;Abuadas and Abuadas, 2019). Several studies were conducted to improve understanding of the barriers that maintain low colorectal cancer screening Editorial Process: Submission:02/15/2021 Acceptance:05/10/2021 rates (Bidouei et al, 2014;Almadi et al, 2015;Reyes and Miranda, 2015;Abuadas et al, 2018;Abuadas and Abuadas, 2019;Al-Hajeili et al, 2019). The perception of CRC risk in the broad community is highly important in ensuring a strong tendency toward screening and prevention.…”
Section: Introductionmentioning
confidence: 99%
“…The perception of CRC risk in the broad community is highly important in ensuring a strong tendency toward screening and prevention. In several studies, most participants perceived themselves as good physically and believed that CRC screening was unnecessary (Bidouei et al, 2014;Almadi et al, 2015;Reyes and Miranda, 2015;Abuadas et al, 2018;Abuadas and Abuadas, 2019;Al-Hajeili et al, 2019).…”
Section: Introductionmentioning
confidence: 99%